AN EXAMINATION OF THE EFFECTS OF OWNERSHIP STRUCTURE AND FINANCIAL LEVERAGE ON THE DIVIDEND POLICIES OF LISTED FIRMS IN NIGERIA - Uwalomwa Uwuigbe (Universitas Hayam Wuruk Perbanas, 2013)
In an attempt to provide a developing economy perspective to the corporate dividend puzzle, thisstudy basically examined the effects of ownership structure and financial leverage on the dividendpayouts of firms operating in Nigeria. Using the judgmental sampling technique, a sampleof 50 selected listed firms from the Nigerian Stock Exchange Market where analyzed using theannual reports for the period 2006 to 2010. The choice of the selected firms’ arises based on thecapital structure and the availability of data for the listed firms. The regression analysis methodwas employed as a statistical technique for analyzing the data collected from the annual report ofthe selected firms. Findings from the paper revealed that there is a significant positive relationshipbetween ownership structure and the dividend payout of the sampled firms in Nigeria. Inaddition, the paper revealed that there is a significant negative relationship between financialleverages and the dividend payout of firms. Thus the paper concludes that while the ownershipstructure of firms in terms of equity interest appear to have a visible and significant effect ondividend payout of firms, on the other hand, the financial leverage have a very significant negativeimpact on firms corporate dividend payout policies.